Content and structural characteristics of emotional intelligence of male and female adolescents with aggressive and self-defeating humor styles - Khonski, Sergey I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The paper presents results of empirical research of sex differences in emotional intelligence among individuals with aggressive and self-defeating humor styles. The author combines trait and ability measures of emotional intelligence. The essential components and structures of emotional intelligence of male and female adolescents’ maladaptive humor styles are established. The correlation between some components of emotional intelligence and aggressive humor style of adolescents are described. The correlation between some components of emotional intelligence and self-defeating humor style of adolescents are established. The author gives different arguments explaining causes of results.